INVESTIGATION OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LINGUISTICS - Kholboyeva Iroda Shukhrat Kizi (Western European Studies, 2025)
This article examines the study of phraseological units in English and Uzbek linguistics, focusing on their structure, semantics, and cultural significance. The comparative analysis highlights the similarities and differences in phraseological expressions in these languages, emphasizing their role in reflecting national identity, worldview, and linguistic heritage.
Keywords: phraseological units; English linguistics; Uzbek linguistis